2012
DOI: 10.1097/phh.0b013e3182461cf2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2008–2010 Economic Recession on Local Health Departments

Abstract: We measured the impact of the 2008-2010 economic recession on local health departments (LHDs) across the United States. Between 2008 and 2010, we conducted 3 Web-based, cross-sectional surveys of a nationally representative sample of LHDs to assess cuts to budgets, workforce, and programs. By early 2010, more than half of the LHDs (53%) were experiencing cuts to their core funding. In excess of 23 000 LHDs jobs were lost in 2008-2009. All programmatic areas were affected by cuts, and more than half of the LHDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 6 publications
0
72
0
Order By: Relevance
“…Between 2008 and 2010, three cross-sectional surveys of a nationally representative sample of local health departments observed more than half were experiencing cuts to "core funding" activities that included basic services related to disease surveillance and local health statistics record-keeping. 188 In excess of 23,000 local health departments jobs were lost in 2008 and 2009. More than half of the departments had to reduce or eliminate at least one programmatic area, such as infectious disease surveillance.…”
Section: Other Social Protection Programsmentioning
confidence: 99%
“…Between 2008 and 2010, three cross-sectional surveys of a nationally representative sample of local health departments observed more than half were experiencing cuts to "core funding" activities that included basic services related to disease surveillance and local health statistics record-keeping. 188 In excess of 23,000 local health departments jobs were lost in 2008 and 2009. More than half of the departments had to reduce or eliminate at least one programmatic area, such as infectious disease surveillance.…”
Section: Other Social Protection Programsmentioning
confidence: 99%
“…D uring times of economic downturn, the consumption of goods and services, including medical care, has been shown to decrease significantly (1)(2)(3). Recent studies have confirmed this pattern for the use of routine, nonurgent services such as screening colonoscopy and dental care (4)(5)(6)(7).…”
mentioning
confidence: 82%
“…Several organizations (e.g., National Association of County and City Health Officials, American Heart Association) track and report information on the occurrence and nature of partnerships with health-sector organizations. These data have been used to assess the number of sectors to which health agencies are connected in communities (Willard et al, 2012). The literature also provides ample evidence that government and nongovernmental organizations working together is a key factor in building a Culture of Health.…”
Section: Number and Quality Of Partnershipsmentioning
confidence: 99%